Understanding Self-gift Consumer Behaviour (SGCB) in Islamic Religious Occasions: Ramadan & Eid - Al-Yafai, Rana (2014)
This dissertation aims to understand self-gift consumer behaviour (SGCB) in Islamic religious occasions; in particular, during Ramadan and Eid. In specific, it is aiming to understand its nature, the motivations that trigger this behaviour and finally the emotions associated with such behaviour.